Third year health care students’ knowledge, surrounding genital warts and cervical cancer risks, the association and role of the human papillomavirus (HPV) and their perceptions of acceptability concerning the HPV vaccine: An empirical study - Kenney, Lauren (2011)
A review of the literature surrounding the human papillomavirus (HPV), suggested that a vaccine to prevent infection was not readily accepted. Inadequate knowledge regarding cervical cancer, genital warts and HPV infection was identified from the existing literature. However, the majority of research focused on parental views and was conducted outside of the UK. With this in mind, the purpose of this study was to investigate third year health care students‟ knowledge, surrounding genital warts and cervical cancer risks, the association and role of HPV and their perceptions of acceptability concerning the HPV vaccine. Such a study was considered important, to determine whether health care students had enough sexual health knowledge, to utilise public health policies once qualified. The study adopted a quantitative methodology. An online questionnaire was made available via an emailed web link, to all third year health care students studying midwifery, pharmacy, physiotherapy, medicine and MNurSci at the University of Nottingham. The data was then collected from a sample of 152 respondents and analysed statistically. The findings from this research provided evidence that: 1) Knowledge surrounding the risk factors for developing cervical cancer was relatively high; 2) There was generally a poor understanding of HPV infection; 3) The majority of participants looked favourably upon the HPV vaccine, despite incomplete sexual health knowledge. The main conclusion drawn from this study was that, once qualified, health care students would be able to implement health policies, regardless of their sexual health knowledge. This dissertation suggests that more widespread sexual health education may be valuable for promoting vaccine acceptance. However, further research exploring the perceptions of the younger age groups, which the vaccine is aimed at, may be beneficial (Racktoo and Coverdale, 2009).